Legal protection for motor vehicle taxpayers in East Java subject to progressive rates - Herman Setiawan (Central Research Institute for Agriculture (CeRIA), 2022)
In this thesis, the matter discussed is legal protection for taxpayers in the event of an error in collecting motorized vehicle tax. Motor Vehicle Tax Collection has fulfilled legal certainty, this is based on article 5 paragraph of Law Number 28 of 2009 in conjunction with Article 6 of East Java Regional Regulation Number 9 of 2010 which regulates the contents of determining the principal amount of motorized vehicle tax. The way to determine it is to multiply the tax base with the motor vehicle tax rate regulated in Article 7 of the East Java Regional Regulation 9 of 2010 concerning Regional Taxes. If the taxpayer owns a 4 (four) wheeled personal motorized vehicle as well as a 2 (two) wheeled motorized vehicle with cylinder contents of 250 cc and above, the second and so on, according to Article 8 of the East Java Regional Regulation 9 of 2010 concerning Regional Tax, the taxpayer is subject to a progressive rate. whose order of tariffs is regulated in the same. In the context of collecting Motor Vehicle Tax with Progressive Rates, there are several legal issues that arise, including the problem of progressive tariff sequences.